A coordinated multiorgan metabolic response contributes to human mitochondrial myopathy - Nneka Southwell; Guido Primiano; Viraj Nadkarni; Nabeel Attarwala; Emelie Beattie; Dawson Miller; Sumaitaah Alam; Irene Liparulo; Yevgeniya I Shurubor; Maria Lucia Valentino; Valerio Carelli; Serenella Servidei; et al. (EMBO Molecular Medicine)
Abstract Mitochondrial diseases are a heterogeneous group of monogenic disorders that result from impaired oxidative phosphorylation (OXPHOS). As neuromuscular tissues are highly energy‐dependent, mitochondrial diseases often affect skeletal muscle. Although genetic and bioenergetic causes of OXPHOS impairment in human mitochondrial myopathies are well established, there is a limited understanding of metabolic drivers of muscle degeneration. This knowledge gap contributes to the lack of effective treatments for these disorders. Here, we discovered fundamental muscle metabolic remodeling mechanisms shared by mitochondrial disease patients and a mouse model of mitochondrial myopathy. This metabolic remodeling is triggered by a starvation‐like response that evokes accelerated oxidation of amino acids through a truncated Krebs cycle. While initially adaptive, this response evolves in an integrated multiorgan catabolic signaling, lipid store mobilization, and intramuscular lipid accumulation. We show that this multiorgan feed‐forward metabolic response involves leptin and glucocorticoid signaling. This study elucidates systemic metabolic dyshomeostasis mechanisms that underlie human mitochondrial myopathies and identifies potential new targets for metabolic intervention.